Effect of several post-harvest technologies on the food quality and safety of edible flowers - Fernandes, Luana (2021)
Edible flowers have been used in food since ancient times. Currently, their consumption has increased in less traditional countries in what regards this practice, as a result of the growth and development of gastronomic market and by the gourmet chefs, who begin to use edible flowers in their dishes, due to their beauty and taste. However, it is a very perishable product, whose quality and safety need to be guaranteed. In this order, the main objective of the present work was to test several post-harvest technologies (separately and combined) to different edible flowers species, according to their seasonal availability, with the purpose of increasing their shelf life. Several studies were carried out in order to perform the physico-chemical characterization of some edible flowers during flowering involving: high hydrostatic pressures (HHP), dehydration (osmotic dehydration (OD), crystallization, freeze drying, hot air convective drying and drying at room temperature (shade)), edible coatings and freezing. Afterwards, the effect of these technologies in some physico-chemical and biological properties of flowers was evaluated, after treatments and during storage. At the end, sensory studies were carried out involving consumers and chefs, with the purpose of evaluating the acceptability and preference. The results indicated that water was the main macronutrient found in the studied flowers; however, other components such as proteins, fibers and carbohydrates, as well as, bioactive compounds (carotenoids, fatty acids, vitamin E, flavonoids, anthocyanins), volatile compounds and free sugars were also detected and quantified. In some situations, significant differences between different flower species and flowering stages were observed. Furthermore, in some situations, some relationships were found between volatiles and bioactive compounds with the sensory perception of the flowers. Regarding the application of post-harvest technologies, the high hydrostatic pressures showed to be a promising technology to increase the shelf life of pansies, while borage and camellia showed to be more susceptible to the high pressures. On the other hand, the application of osmotic dehydration to pansies did not produce the desired effects due to the presence of superhydrophobic papillae; however, crystallization proved to be a promising technology for their preservation. Regarding centaurea, shade drying was the most promising method, since the highest concentrations of bioactive compounds were obtained. Concerning borage petals, freeze-drying showed to be a promising method to produce dried flowers for infusions. The application of low temperatures was also tested, namely freezing (in ice cubes and in their natural form), and it was generally observed that the flowers in ice cubes maintained a similar appearance to fresh ones for a longer period of time than naturally frozen. With regard to treatment with edible coatings, the alginate was tested in pansies. This treatment gave good results, having the coated and packed flowers increased the shelf life by 7 days more than the fresh ones. It was also tested the effectiveness of the combined application of preservation processes, namely the application of high hydrostatic pressures as a pretreatment to osmotic dehydration, and the simultaneous application of the two treatments to pansies. The results indicated that the combination of high hydrostatic pressures with osmotic dehydration to pansies resulted in more fragile flowers. However, the application of high hydrostatic pressures as pretreatment to osmotic dehydration may be a promising technology for this flower species. Finally, some chefs and consumers were submitted to an organoleptic test of pansies subjected to different post-harvest technologies. The chefs and consumers presented different sensory profiles, both of which liked more the pansies treated with high hydrostatic pressures than those coated with alginate and crystallized. However, consumers also rated the pansies subjected to the last two processes with good scores. In conclusion, the results of this work allowed demonstrating the potential of several post-harvest technologies in the preservation of some edible flowers, without compromising their physicochemical and biological properties and with great possibility of being accepted by the potential users.